Diseño y construcción de una ontología para formalizar relaciones de influencia entre desórdenes del sueño y enfermedades desde el dominio médico (2020)
There are a large number of research publications in the medical field. This makes it difficult for a researcher to find relevant research articles. On the other hand, currently in the biomedical ontologies investigated, there is no formal knowledge representing the relationships of influence between sleep disorders and diseases. Given this second problem, it was proposed to design and build an ontology that formally represents this domain of knowledge, and later integrate it with some of the already existing ontologies to enrich this knowledge.--Taken from the Degree Document Format.